RETRACTED: How Does Algerian Trade Respond to Shocks in Oil Prices and Uncertainty? - Wang, Ke; Liu, Zhen; Wei, Zhen; Lou, Siyuan; Hicham, Ayad; Aissa, Djedaiet; Meo, Muhammad Saeed (Frontiers in Environmental Science, 2022)
This study aims to investigate the nexus between oil prices and the world uncertainty index, as well as their impact on imports and exports in Algeria over the period 1990Q01 to 2020Q04. The ARDL model and its extensions, such as the Fourier ARDL, the NARDL, and the MTNARDL models, were applied in this study to provide robust outputs. The outcomes reveal various results. Firstly, oil prices affect uncertainty only in negative and extremely small changes with a negative association. Secondly, positive and extremely large changes in oil prices increase exports and imports in the long and short-run terms. Thirdly, both extremely small and large changes in uncertainty affect imports in the long and short run. Finally, negative oil price shocks have an indirect impact on imports via their effect on uncertainty.